2020
DOI: 10.1002/jclp.22926
|View full text |Cite
|
Sign up to set email alerts
|

A pilot investigation of universal school‐based prevention programs for anxiety and depression symptomology in children: A randomized controlled trial

Abstract: Objective: The current study aimed to provide a preliminary evaluation of two universal school-based prevention programs, Emotion Regulation (ER) and Behavioral Activation (BA), by increasing resilience to manage excessive worry, a transdiagnostic feature across anxiety and depression.Method: Primary school children (N = 295; 52.5% female; 8-13 years) from five Australian schools were cluster randomized to an ER, BA or usual class control condition.Outcome measures included resilience, worry, anxiety, and depr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 86 publications
1
13
0
1
Order By: Relevance
“…In this systematic review, we included 17 RCTs. Four studies were published in 2019 ( Adibsereshki et al, 2019 ; Druker et al, 2019 ; Volanen et al, 2019 ; Zhang et al, 2019 ); two each in 2013 ( Anticich et al, 2013 ; Lee and Stewart, 2013 ), 2014 ( Castro-Olivo, 2014 ; Chen et al, 2014 ), 2015 ( Leventhal et al, 2015 ; Tan and Martin, 2015 ), 2018 ( Hood et al, 2018 ; Yeun and Woo, 2018 ), and 2020 ( Hatamizadeh et al, 2020 ; Johnstone et al, 2020 ). Only one study was published in 2010 ( Hyun et al, 2010 ), 2016 ( Chisholm et al, 2016 ), and 2017 ( Li et al, 2017 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this systematic review, we included 17 RCTs. Four studies were published in 2019 ( Adibsereshki et al, 2019 ; Druker et al, 2019 ; Volanen et al, 2019 ; Zhang et al, 2019 ); two each in 2013 ( Anticich et al, 2013 ; Lee and Stewart, 2013 ), 2014 ( Castro-Olivo, 2014 ; Chen et al, 2014 ), 2015 ( Leventhal et al, 2015 ; Tan and Martin, 2015 ), 2018 ( Hood et al, 2018 ; Yeun and Woo, 2018 ), and 2020 ( Hatamizadeh et al, 2020 ; Johnstone et al, 2020 ). Only one study was published in 2010 ( Hyun et al, 2010 ), 2016 ( Chisholm et al, 2016 ), and 2017 ( Li et al, 2017 ).…”
Section: Resultsmentioning
confidence: 99%
“…Four studies conducted mid-term follow-up (3 to 6 months) (Li et al, 2017;Hood et al, 2018;Volanen et al, 2019;Johnstone et al, 2020), but one study could not be included because the authors did not provide the results of the follow-up (Li et al, 2017). Hood et al (2018) and Volanen et al (2019) Three RCTs conducted long-term follow-up (> 6 months; Anticich et al, 2013;Li et al, 2017;Hood et al, 2018).…”
Section: Follow-up Analysismentioning
confidence: 99%
“…Females are richer in emotional experience and more sensitive to emotional fluctuations. Some surveys have shown that school-related factors play a significant role in adolescent mental health [45][46][47]. Severe anxiety may disturb the study and life of adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…Schools should strengthen communication and carry out psychological counseling and psychotherapy [48]. The school develops mental health programs which can improve students' positive psychological state and prevent severe anxiety [46,47]. In order to prevent students from severe anxiety, a psychological consultation room should be set up at the school.…”
Section: Discussionmentioning
confidence: 99%
“…Faktor percaya diri ini berhubungan dengan kepercayaan diri saat melepaskan anak panah, Berdasarkan penelitian Green (2020) terdapat hasil yang signifikan dari hubungan kepercayaan diri ini dalam kepercayaan diri pada siswa. Selaras dengan penelitian Johnstone et al (2020) tingginya tingkat percaya diri akan berdampak pada keberhasilannya, sedangkan siswa yang memiliki kepercayaan diri rendah akan mempengaruhi keberhasilannya dalam mencapai hasil yang maksimal. Senada dengan penelitian Wolfson et al, (2021;Yachsie et al, (2021) menyatakan bahwa jika kepercayaan diri seseorang terganggu maka konsentrasi saat melakukan pembelajaran maupun tehnik panahan akan berdampak pada hasil.…”
Section: Faktor Percaya Diriunclassified